Incorporating informal operations in public transport system transformation: the case of Cape Town, South Africa - Wilkinson, Peter (Revista Brasileira de Gestão Urbana, 2017)
Efforts in Cape Town to bring about a fundamental transformation of the existing fragmented and relatively dysfunctional public transport system to a comprehensively planned ‘integrated rapid transit’ system, which includes the introduction of bus rapid transit services as a key component, have encountered certain institutionally embedded obstacles. This paper briefly outlines the nature of these problems, focusing in particular on the difficulties experienced in engaging with, and effectively incorporating, informal minibus-taxi operations which serve a significant segment of the city’s public transport passenger market. It seeks to draw out the main policy implications, as well lessons which might be taken up elsewhere, in other initiatives to address the differentiated mobilities and travel patterns which shape the ‘urban transport divide’ in many cities of the ‘global South’